2017
DOI: 10.1016/j.biocon.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Habitat features act as unidirectional and dynamic filters to bat use of production landscapes

Abstract: Conserving global biodiversity requires careful management of production landscapes, especially in this era of rapid environmental change. The habitat filtering framework has been used for predicting species responses to land-use changes. Habitat filters are essentially features that may slow, or limit, species use of certain habitats. We wanted to determine if this framework could identify habitat and landscape filters that predicted bat use of restored forest at the species-specific and trait group levels. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This microbat species’ foraging behaviour therefore requires an uncluttered flight path, which may explain its negative correlation with vegetation structural diversity SWDI and canopy density in the present study, as well as its reduced activity in the jarrah forest in restored mine‐pits which have very high midstorey cover (Burgar et al . ). Alternatively, tree decline may indirectly affect F .…”
Section: Discussionmentioning
confidence: 97%
“…This microbat species’ foraging behaviour therefore requires an uncluttered flight path, which may explain its negative correlation with vegetation structural diversity SWDI and canopy density in the present study, as well as its reduced activity in the jarrah forest in restored mine‐pits which have very high midstorey cover (Burgar et al . ). Alternatively, tree decline may indirectly affect F .…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, we located roost cavities on young trees with small girths that would ordinarily be removed during thinning interventions. Tree age can be considered a unidirectional habitat filter (Pereira et al, 2004;Burgar et al, 2017) for tree-dwelling bats and so the value of young trees should be considered carefully in management plans to encourage the natural succession of veteran and standing dead trees and to provide sufficient turnover of suitable cavities over time. The use of artificial roosts such as bat boxes may be appropriate in young woodland to increase roosting opportunities for bats while waiting for the wood to mature naturally, although consideration should be given to the type of box and scale of use to ensure that rare species such as barbastelles are not unintentionally disadvantaged.…”
Section: Recommendations For Managementmentioning
confidence: 99%
“…Bats are not homogeneously distributed across the landscape. For example, bat activity increases with increasing landscape heterogeneity (Burgar et al, 2017;Chaplin-Kramer et al, 2011;Monck-Whipp et al, 2018). Woodland interfaces are important predictors of bat activity (Fill et al, 2022), and one study found that bat activity is 5 times higher in landscapes containing a double row of trees compared to standalone trees (Kalda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%